Inter- and intra-subject variability of motor cortex plasticity following continuous theta-burst stimulation - Vallence, A.-M.; Goldsworthy, M.R.; Hodyl, N.A.; Semmler, J.G.; Pitcher, J.B.; Ridding, M.C. (Neuroscience, 2015)
•Comprehensive study of between-session reproducibility of cTBS-induced plasticity.•150% RMT is the most reliable TMS intensity to probe cTBS-induced plasticity.•cTBS-induced plasticity probed at 150% RMT correlated with perceived stress. Background: The potential of non-invasive brain stimulation (NIBS) for studying, and inducing, functionally relevant neuroplasticity is dependent on protocols that can induce lasting, robust and reliable effects. A current limiting factor is the large inter- and intra-subject variability in NIBS-induced neuroplastic responses. There has been some study of inter-subject response variability and factors that contribute to it; however, intra-subject response variability has, so far, received little investigation. Objectives: By testing participants on multiple occasions we aimed to (1) compare inter- and intra-subject variability of neuroplastic responses induced by continuous theta-burst stimulation (cTBS); (2) determine whether the transcranial magnetic stimulation (TMS) intensity used to measure cTBS-induced neuroplastic responses contributes to response variability; (3) determine whether assessment of factors known to influence response variability can be used to explain some of the variability in cTBS-induced neuroplastic responses across experimental sessions. Methods: In three separate experimental sessions, motor-evoked potential (MEP) input–output (IO) curves were obtained before and after cTBS, and questionnaire-based assessments of physical activity and perceived stress were obtained. Results: cTBS-induced MEP suppression was greatest at the upper end of the IO curve (150–180% resting motor threshold; RMT) and most consistent across subjects and across experimental sessions when assessed with a TMS intensity of 150% RMT. The magnitude of cTBS-induced MEP suppression evoked at 150% RMT correlated with self-reported perceived stress, but not with self-reported physical activity. Conclusions: The most reliable TMS intensity to probe cTBS-induced long-term depression (LTD)-like neuroplastic responses is 150% RMT. This is unlikely to simply be a ceiling effect and, we suggest, may be due to changes in the descending volley evoked at higher stimulus intensities. The perceived stress scale appears to be sufficiently sensitive to measure the influence of subject stress on LTD-like neuroplastic responses.